Comparative genomics of Fusarium oxysporum f. sp. melonis strains reveals nine lineages and a new sequence type of AvrFom2. (8th December 2020) - Sabahi, Fatemeh; Sain, Mara de; Banihashemi, Zia; Rep, Martijn
Summary: Fusarium oxysporum f. sp. melonis (Fom) is one of the most important pathogens of melon worldwide. In this study, we investigated the genomic diversity of Fom. One of the aims was to find clues for the origin(s) and dispersal of clonal lineages and races of Fom. We therefore included a large number of Fom strains from Iran, where melon has been cultivated for at least 5000 years. In 33 new genome sequences of Fom strains from different geographical regions of Iran and across the world, 40 new candidate effector genes were identified. Presence/absence of candidate effector genes and phylogenetic analyses resolved nine Fom lineages. The presence of a highly similar set of effector genes in some distant lineages is suggestive of horizontal chromosome transfer, a process known to occur in the Fusarium oxysporum species complex. Race 1.2, which breaks both Fom1 and Fom2 resistance genes, occurs in three of the nine lineages, two of which are predominant in Iran. We also identified a new sequence type of the AVRFom2 avirulence gene in one lineage. Expression of this sequence type during melon infection and genetic complementation suggest that this sequence type is not recognized by the Fom2 resistance protein.